2013
DOI: 10.1063/1.4811789
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants of cubic and wurtzite boron nitrides

Abstract: We synthesized pure polycrystalline cubic boron nitride (cBN) and wurtzite boron nitride (wBN) by the direct conversion method from hexagonal boron nitride, and measured their longitudinal-wave elastic constants C L between 20 and 300 K using picosecond ultrasound spectroscopy. Their room-temperature values are 945 6 3 GPa and 930 6 18 GPa for cBN and wBN, respectively. The shear modulus G of cBN was also determined by combining resonance ultrasound spectroscopy and micromechanics calculation as G ¼ 410 GPa. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 65 publications
5
37
0
1
Order By: Relevance
“…36 Actually, larger-grain specimens include more wBNs, and apparent wBN dependence of C L could be seen. However, we found that the elastic constants of isotropic cBN and wBN are the same in the previous work, 37 insisting that wBN content dependence does not have to be considered. Then, we considered our specimens as composites, including softened pennyshaped inclusions of cBN, simulating grain boundaries, and Fig.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…36 Actually, larger-grain specimens include more wBNs, and apparent wBN dependence of C L could be seen. However, we found that the elastic constants of isotropic cBN and wBN are the same in the previous work, 37 insisting that wBN content dependence does not have to be considered. Then, we considered our specimens as composites, including softened pennyshaped inclusions of cBN, simulating grain boundaries, and Fig.…”
mentioning
confidence: 51%
“…37 The elastic stiffness tensor C C of the composite can be calculated by Eshelby's equivalent inclusion theory using Mori-Tanaka mean field modeling 38,39…”
mentioning
confidence: 99%
“…By adding boron as the lightest and smallest group III element to the currently used AlGaN system, another degree of freedom in band gap and lattice constant tailoring can be utilized. To lattice‐match AlBGaN QWs with an aluminium content of 50% to an AlN barrier, a boron incorporation below 6% would be sufficient . However, the solubility of boron in AlGaN is very low.…”
Section: Introductionmentioning
confidence: 99%
“…Considering state of the art UV‐LED devices, Al x Ga 1− x N quantum wells ( x = 0.4) and barriers ( x = 0.55) have a difference in aluminium composition of Δx=15%. Lattice matching of both layers could be achieved by incorporating only small B amounts of about 2% in the quantum wells assuming the validity of Vegard's law and lattice constants of 0.3112, 0.3189, and 0.2549 nm for the binaries AlN, GaN, and wurtzite BN, respectively . Still, the low solubility, but also parasitic gas phase reactions and low surface mobility of boron, make it very challenging to grow high quality quaternary AlBGaN alloys with appropriate optoelectronic properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation